Food Commodity Competitiveness and Accessibility in Barlingmascakeb - Destiningsih, Rian; Sugiharti, Rr Retno; Achsa, Andhatu (Universitas Negeri Semarang, 2019)
Barlingmascakeb is an institution formed from 5 regions that seeks to improve regional cooperation in exploiting the economic potential between regions. The five members are included in the 11 regions with the highest poverty in 2017 in Central Java. To find out the potential of each region, Klassen Typology, LQ, MRP, overlay, shiftshare E-M, CQ are used. The results of the Klassen Typology show that Cilacap Regency, Banyumas, Purbalingga, Kebumen are included in high growth and high income. LQ shows Banjarnegara Regency has one superior food commodity, one commodity in Purbalingga Regency, one commodity in Banyumas Regency, four in Cilacap Regency and ten commodities in Kebumen Regency. MRP shows that the commodity of paddy rice is growing rapidly in four Regencys, soybean commodities in four Regencys, green bean commodities in two Regencys, egg-broiler commodities in three Regencys, broiler commodities in four Regencys, duck commodities in four Regencys. Overlay shows dominant food commodities growth in Banjarnegara Regency 2 commodities, Purbalingga 4 commodity Regency, Banyumas Regency 5 commodities, Cilacap Regency 4 commodities, Kebumen 6 commodity Regency. Shiftshare EM shows a competitive and specialized sector in Banjarnegara Regency there are 9, Banyumas Regency there are 12, Cilacap Regency there is 1, Purbalingga Regency there are 4, Kebumen Regency there are 5. CQ shows that Purbalingga Regency has a favorable position in interacting with the Regency members of Barlingmascakeb regional institutions.